Comparison of different electric vehicle integration approaches in presence of photovoltaic and superconducting magnetic energy storage systems. (1st July 2020) - Salama, Hossam S.; Vokony, István
Abstract: The impacts of electric vehicles on the electrical power network in the presence of renewable energy sources and energy storage systems is a field to be studied in depth. Especially because in recent years the installation of electric vehicles has increased considerably in order to reduce the emission of CO2 and fossil fuel consumption to reach environmental cleanliness. This paper presents a comparison between the different integration methods of electric vehicles subject to the availability of photovoltaic systems and superconducting magnetic energy storage systems. Moreover, it analyses and explains the issues of power loss, voltage fluctuation, load levelling and reactive power support in the different approaches. Besides that, this study explores the role of superconducting magnetic energy storage systems in different cases. A fuzzy logic control algorithm is proposed to estimate the charging and discharging process of superconducting magnetic energy storage systems and electric vehicles. In addition, a coordinated control system is proposed to manage the power between the photovoltaic system, the electric vehicles and superconducting magnetic energy storage system as well as boost the power system performance. A whole coordinated control system based on fuzzy logic control is proposed to make the power management of the grid, EVs, SMES, and PV in an all integration approach of electric vehicles to achieve the improvements in the power system performance and maintain the reliability and sustainability of the all system components. Finally, the data analysis of the simulation results, performed by the Matlab Simulink toolbox is presented in all cases to explain the performance of the superconducting magnetic energy storage system, the control system, power losses, voltage fluctuation and reactive power support. Highlights: Introduce a brief review of EV integration approaches. Indicates the effect of EV integration approaches on the power system. Proposes an FLC algorithm control EVs and SMES. Power management between grid, EVs, SMES, and PV using coordinated FLC. A comparison and statistical analysis are presented for all types of EV integration approaches.